2019
DOI: 10.1159/000495992
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Free Amino Acids and Urea Derived from Isolated Corneocytes of Healthy Young, Healthy Aged, and Diseased Skin

Abstract: Background/Aims: Free amino acids (FAAs) and urea, present inside the corneocytes, can be important indicators of skin condition. However, due to the lack of a standard extraction protocol for FAAs from corneocytes, conflicting research results have been reported. Therefore, the purpose of this study was (1) to standardize the extraction protocol and (2) to investigate FAA profiles in healthy young and healthy old volunteers, as well as in psoriasis and atopic dermatitis patients. Methods: Skin samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…In general, the present study revealed that FAAs for cosmeceutical applications can be obtained from several nature-based resources. As reported by Hussain et al (2019), the concentration of each FAA in the stratum corneum of healthy human skin is less than 10.00 nmol/mg indicating that only very low amount of these bioactive molecules are required in formulations pertaining to replacement therapies for the treatment of dry skin conditions. As can be seen from the results in Table 1, natural resources including but not limited to oyster mushroom, broccoli, garlic, Ethiopian onion, ginger, cabbage, cumin, and decoco contain a significant amount of most of the FAAs.…”
Section: Malus Domesticamentioning
confidence: 90%
See 1 more Smart Citation
“…In general, the present study revealed that FAAs for cosmeceutical applications can be obtained from several nature-based resources. As reported by Hussain et al (2019), the concentration of each FAA in the stratum corneum of healthy human skin is less than 10.00 nmol/mg indicating that only very low amount of these bioactive molecules are required in formulations pertaining to replacement therapies for the treatment of dry skin conditions. As can be seen from the results in Table 1, natural resources including but not limited to oyster mushroom, broccoli, garlic, Ethiopian onion, ginger, cabbage, cumin, and decoco contain a significant amount of most of the FAAs.…”
Section: Malus Domesticamentioning
confidence: 90%
“…Methionine (Met), cysteine (Cys), and tryptophan (Try) are present in smallest concentrations; and proline (Pro) is obscured because of the large amount of Cit masking its presence. Twenty-three (23) FAAs were detected in human corneocytes of 4 different study groups in a study by Hussain et al (2019) at different concentrations. The level of NMFs including FAAs can decline in dry skin conditions due to many disease conditions such as atopic dermatitis, ichthyosis vulgaris, psoriasis, and age in addition to environmental conditions (Verdier-Sévrain and Bonté 2007; Kwan et al 2012;Takada et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indoor sources of amines, in addition to outdoor‐to‐indoor transport, include smoking 404‐408 ; cooking 274,313,409,410 ; anticorrosive agents used in humidification or HVAC units 411‐413 ; textiles and textile carpet tiles 414,415 ; and the decomposition of casein‐containing building materials 416 . Amines, amino acids, and urea are also known constituents of human skin 417‐422 . These compounds are used as active agents in personal care products, including skin moisturizers 423 …”
Section: Acids and Basesmentioning
confidence: 99%
“…416 Amines, amino acids, and urea are also known constituents of human skin. [417][418][419][420][421][422] These compounds are used as active agents in personal care products, including skin moisturizers. 423…”
Section: Indoor Sources Of Aminesmentioning
confidence: 99%
“…Avaliações morfológicas constituem etapa fundamental de quaisquer pesquisas dermatológicas veterinárias por permitirem a descrição estrutural dos elementos que compõem a pele, favorecendo a padronização de características de normalidade intraespecíficos (KAMP et al, 2009). De uma forma geral, as camadas e estratos da pele têm sido objeto de muitos estudos morfológicos e ultraestruturais, tanto pela variabilidade entre as espécies, quanto às funções imunológica, farmacodinâmica e farmacocinética cutânea (HUSSAIN, 2019;CHANG, 2017;AGARWAL, 2019;LOGGER, 2019). Em medicina veterinária, dado o elevado número de espécies estudadas, tais características tornam-se ainda mais relevantes, haja visto que as variações de celularidade, densidade celular, volume celular e tecidual, influenciam na fisiologia cutânea e, consequentemente, na rotina clínica para a espécie (KAMP et al, 2011).…”
Section: Introductionunclassified